Quando a linguística encontra a linguagem: da escrita de Émile Benveniste presente no dossiê Baudelaire ao estudo semiológico de uma obra literária - Vier, Sabrina (Universidade do Vale do Rio dos Sinos, 2016)
In 1992, Émile Benveniste’s manuscripts about poetic language were disclosed and generated what today is known as Baudelaire Dossier. This material was deposited at the National Library of France in 2004, and publicized in 2008 through Chloé Laplantine’s thesis and in 2011 by Lambert-Lucas publishing house. The Baudelaire Dossier, probably a Benveniste’s study for a paper commissioned by Roland Barthes for Langages magazine, consists of 367 folios. A few studies have shown that the dossier presents a Benveniste’s research into Baudelaire’s discourse. Going beyond that finding, this thesis aims to investigate how Benveniste’s writing in the dossier can be delineated as a semiological study of a work and, thus, a study on the poetical in language. The analysis category, inspired by Fenoglio (2009)and by Nietzsche (2009, 2007, 2004), it is named rumination, because is by means of enunciation insistence verified in writing Benveniste to be established the enunciation facts for analysis. The corpus is not composed of the total of folios, rather, it comprises those evidencing terms and procedures ruminated in Benveniste’s writing. Of the 159 selected folios, two research perspectives have been selected for analysis: (i) both the particularity and singularity of Baudelaire’s discourse, and (ii) the radically specific character of the poetic language. Regarding the former, the most ruminated procedures were: (a) the selection of images, and (b) the search for the structure of the whole work. Concerning the latter, two aspects seemed to be repeatedly addressed in Benveniste’s writing: (a) nature, and (b) the functioning of the poetic language. The following results could be evidenced: the particularity and singularity of Baudelaire’s discourse are due to both the image of the mirror, which engenders the other images, and the relationships between time, sonority and invocation, which point out the primordial correspondence: the man and the world. The correspondence is thus the principle structuring Baudelaire’s poetic universe. These results has brought into play the radically specific character of the poetic language: the material ¬– the written word–, the unity – the icon word – and the functioning principle ¬¬– the iconicity. It is verified so that the Benveniste writing shows a semiological study of poetic language from a linguistic perspective that transcends the saussurian sign and reaches emotion and human experience.
Keywords: Linguagem; Semiologia; Linguística; Dossiê Baudelaire; Poético; Language; Semiology; Linguistics; Baudelaire dossier; Poetic; ACCNPQ::Lingüística, Letras e Artes::Lingüística